ITIKAD BAIK DALAM PROSES MEDIASI PERKARA PERDATA DI PENGADILAN - Ajrina Yuka Ardhira; Ghansham Anand (Universitas Airlangga, 2018)
Mediation is a duty which must be taken by the parties wishing to settle its dispute in the Court as specified in the Civil Procedure Code and in accordance with Article 130 HIR and 154 RGB. To improve the regulation of mediation in the Court, the Supreme Court shall issue its Regulation, namely the Supreme Court Regulation No. 1 of 2016 on Mediation Procedures in the Court. Where the regulations on mediation as stipulated in the Supreme Court Regulation No. 1 of 2016 use good faith in its formal conditions. And with such a condition the Supreme Court expects the success rate of mediation in the first level to increase so as to reduce the number of cases accumulated at the Supreme Court. Good faith as a duty to the parties in the Supreme Court Regulation Number 1 Year 2016 is made clear in Article 7 paragraph (1), where there are legal consequences for parties that are considered not having good intentions by doing things listed in Article 7 paragraph (2) , namely Article 22 for the plaintiff and Article 23 for the defendant.